If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5 + -3x) = 9 + -6x (5 * 2 + -3x * 2) = 9 + -6x (10 + -6x) = 9 + -6x Add '6x' to each side of the equation. 10 + -6x + 6x = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 10 + 0 = 9 + -6x + 6x 10 = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 10 = 9 + 0 10 = 9 Solving 10 = 9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -7.6=5.3+x+7.34 | | 4x+6(x+40)=180 | | 6t-32=7t-50 | | 5c=c+52 | | 3(2x-8)=2(3x+8) | | 2(sqrt(x))-5=x | | 7x-1=2x-3 | | 5-3x=3x-25 | | 527=31n | | 2x-3=6+2x | | -80.2-9x=1.7 | | 10x-75=51+4x | | o=5-(2x-17) | | x+3.07+2.5=1.8 | | -80.2-9x=-21.9 | | 10a+55b= | | 3x+7-9x=-11 | | x+43=87 | | x+5=1.5x+2.5 | | 10f+2(5f+8)=-10f-4(2f-30) | | 5d+9=24 | | 2=17 | | 8ex=7 | | p*(q+r)=qp+pr | | y^2+9xy+18x^2=0 | | 32860-0.06x=x | | 7y+5=6y | | -43+11x=6x+32 | | -2k-16=3h-6 | | 2(x+4)=12x+62 | | 46=-6-8 | | 269.50=14 |